Analysis of 2019 Common Hope Language Institute Students’ Understanding of Chinese Internet Language Characters and Symbols: 共同希望语言学院 2019 届学生对汉语网络语言汉字类与符号类的理解分析 - Chelsi Fidelis; Sabinus Iden (Published by Confucius Institute UNS, 2025)
The way a community uses the internet influences language, causing changes in how words are used online. Although online expressions may originate from Chinese, the usage of Chinese internet language differs greatly from that of everyday Chinese. Therefore, learners of Chinese must understand internet language in order to communicate effectively. This study aims to understand the level of comprehension of Chinese internet language among the 2019 cohort of students at the Joint Hope Language Institute. After summarizing the categories of Chinese internet language, data were collected through distributed questionnaires and test items. Based on the survey conducted with the 2019 cohort of students at the Joint Hope Language Institute, the results indicate that most students still have a relatively low level of understanding of the logographic and symbolic categories of Chinese internet language, particularly in the categories of old words with new meanings and homophones. In addition, students in the institute receive limited instruction on Chinese internet language, focusing primarily on traditional Chinese and linguistics.